Analisis Daya Keluaran PLTS–Turbin Angin terhadap Suhu Kotak Pendingin Portable Terintegrasi GPS IoT: Indonesia - Mas Ahmad Baihaqi; Hartawan Abdillah Abdillah; Adi Mulyadi; Tamam Asrori Asrori; Alief Muhammad; Ahmad Fauzan; M. Bayu Afandi (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2025)
The main challenge faced by small-scale fishermen in Probolinggo is the deterioration of fish catches due to limited cooling systems. This study developed a portable cooling box powered by a hybrid solar–wind energy system integrated with GPS–IoT. The system was designed using a 100 Wp solar panel, a 450 W wind turbine, a 100 Ah battery, a 3000 W inverter, and temperature sensors with IoT communication modules for real-time monitoring. Experiments were conducted for 12 hours under three operating modes: solar, wind only, and hybrid. The results show the hybrid mode maintained the cooling box temperature below 8 °C for more than 12 hours, while the solar-only and wind-only modes lasted only 4–7 hours. The GPS–IoT integration enabled simultaneous monitoring of vessel location and energy conditions. Therefore, the proposed system proved to be more reliable in preserving fish quality while enhancing efficiency and safety of small-scale fishermen through renewable energy.